2017
DOI: 10.1007/s00261-017-1176-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of the degree of differentiation in colon cancer with dual-energy spectral CT

Abstract: Spectral CT imaging parameters (IC, NIC, and λ ) in AP provide improved accuracy for evaluating the degrees of differentiation in colon cancer than CT number at 70 keV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 22 publications
3
25
0
Order By: Relevance
“…In addition, nICPP has been reported to exert a high sensitivity in differentiating malignant gastric mucosal lesions from normal gastric mucosa [ 11 ]. Furthermore, studies on the diagnostic efficacy of tumor differentiation degree are inconsistent [ 35 , 36 ], which may be due to the different biological behaviors of tumors and degrees of differentiation. A previous study has found that the values of IC and nIC of poorly differentiated adenocarcinoma are not significantly different compared to those of moderately and well-differentiated adenocarcinomas in AP [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, nICPP has been reported to exert a high sensitivity in differentiating malignant gastric mucosal lesions from normal gastric mucosa [ 11 ]. Furthermore, studies on the diagnostic efficacy of tumor differentiation degree are inconsistent [ 35 , 36 ], which may be due to the different biological behaviors of tumors and degrees of differentiation. A previous study has found that the values of IC and nIC of poorly differentiated adenocarcinoma are not significantly different compared to those of moderately and well-differentiated adenocarcinomas in AP [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies demonstrated a significant difference in IC between poorly and moderate/well-differentiated colorectal cancer [ 48 , 49 ]. Chuang-bo et al [ 49 ] only found a significant difference during the arterial phase, while Gong et al [ 48 ] reported a significant difference in both the arterial and the venous phase.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies demonstrated a significant difference in IC between poorly and moderate/well-differentiated colorectal cancer [ 48 , 49 ]. Chuang-bo et al [ 49 ] only found a significant difference during the arterial phase, while Gong et al [ 48 ] reported a significant difference in both the arterial and the venous phase. Similar to the gastric cancer studies [ 42 , 45 ], a positive correlation between IC and pathological grading of rectal cancer prior and following chemoradiotherapy treatment was reported [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations